TREATMENT OPTIMIZATION OF KIDNEY RECIPIENTS WITH PRE-TRANSPLANT PROLONGED ANURIA - A. V. Kolsanov; B. I. Kharitonov; I. A. Bardovsky (Вестник трансплантологии и искусственных органов)
Aim. Оptimize the treatment of patients with prolonged anuria kidney transplantation due to the introduction of the diagnostic algorithm and treatment of patients at risk. Materials and Methods. 145 renal transplant recipients who had surgery during the period from 2006 to 2011. Of these – 73 (50.3%) patients with anu- ria period exceeding 3 years. An algorithm for the treatment of patients with prolonged anuria kidney trans- plantation, which consists of three stages: pre-operative, peri-operative and post-operative. In the study, two groups. The first group of 47 patients, which were held all three stages of the algorithm evaluation and treat- ment of patients with prolonged anuria in kidney transplantation. The second group of 26 patients with pro- longed anuria without urological examination and treatment. Results. Implementation of the proposed algo- rithm of diagnosis and treatment of patients with prolonged anuria can reduce the risk of adverse outcome of 11. Additional specific urological examination and treatment can reduce the number of urological com- plications, both in the immediate and late postoperative period by 20%. The emergence of severe urological complications in patients with prolonged anuria increases the risk of adverse outcome of 17. The most pre- ferred anastomosis urinary tract in recipients were on long-term renal replacement therapy is an immersion- type anastomosis «drop in». Renal transplant patients with prolonged anuria preferable to perform up to 45 ye- ars, as this reduces the relative risk of an adverse outcome by 14 times compared with the older age group.Conclusion. Prolonged anuria in a patient with chronic renal failure awaiting a kidney transplant, is not a con- traindication to the operation. The duration of anuria not significantly affect the results of renal transplantation.